2019
DOI: 10.1101/735084
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multivoxel patterns for perceptual confidence are associated with false color detection

Abstract: While it has been proposed that metacognition and conscious perception are related, the mechanistic relationship between the two is unclear. To address this question, we combined decoded neurofeedback (DecNef) in functional magnetic resonance imaging (fMRI) with concurrent psychophysics. Participants were rewarded for activating multivoxel patterns for color discrimination confidence while they detected color in mostly achromatic stimuli. We found that occurences of voxel patterns for high color discrimination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Participants progressively improved in their ability to induce neural patterns that were similar to the target concept (i.e., dogs). This observation is noteworthy because previous DecNef studies that used a similar amount of training sessions as here (Amano et al, 2016; Cortese et al, 2016; Knotts et al, 2019; Koizumi et al, 2016; Taschereau-Dumouchel et al, 2018), did not reliably observe significant learning effects, despite observing DecNef effects on behavioral performance. Here we used an improved decoder to provide a better calibrated and more fine-grained feedback to participants (Margolles et al, 2023).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Participants progressively improved in their ability to induce neural patterns that were similar to the target concept (i.e., dogs). This observation is noteworthy because previous DecNef studies that used a similar amount of training sessions as here (Amano et al, 2016; Cortese et al, 2016; Knotts et al, 2019; Koizumi et al, 2016; Taschereau-Dumouchel et al, 2018), did not reliably observe significant learning effects, despite observing DecNef effects on behavioral performance. Here we used an improved decoder to provide a better calibrated and more fine-grained feedback to participants (Margolles et al, 2023).…”
Section: Discussionsupporting
confidence: 55%
“…Because of this, we elected to include a control group of participants that did not undergo DecNef in order to test that the behavioral pattern of search performance in the DecNef group was indeed specific to DecNef training. Note that a similar approach was used in prior associative DecNef studies (Amano, Shibata, Kawato, Sasaki, & Watanabe, 2016; Knotts, Cortese, Tascherau-Dumouchel, Kawato, & Lau, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our ultimate, and possibly long-term scientific goal is to cause phenomenal consciousness by decoded neurofeedback without sensory stimuli or motor tasks. Knotts et al (2019) obtained intriguing results toward this direction, finding that reinforcing mental representations of high confidence and a stimulus feature (e.g., the color red) was associated with a higher chance of making false alarms. Yet, this study also showed that the goal of generating phenomenal consciousness is probably too difficult without explicit computational models like CRMN.…”
Section: Discussionmentioning
confidence: 99%
“…, 2008b ) or using multiple brain decoders. This later possibility was notably explored in a previous experiment ( Knotts et al. , 2019 ).…”
Section: Future Applicationsmentioning
confidence: 94%